2014
DOI: 10.1364/ao.53.000b12
|View full text |Cite
|
Sign up to set email alerts
|

Laser speckle probes of relaxation dynamics in soft porous media saturated by near-critical fluids

Abstract: Speckle correlation analysis was applied to study the relaxation dynamics in soft porous media saturated by near-critical carbon dioxide. The relaxation of soft matrix deformation was caused by a stepwise change in the fluid pressure. It was found that the deformation rate in the course of relaxation and the relaxation time strongly depend on the temperature of the system. The values of relaxation time reach their maximal values in the vicinity of the critical point of saturating fluid. The contributions of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…On the contrary, following from the data presented in Figure 3 for the SiO2-based system, it can be concluded that its diffuse transmittance cannot be adequately described in terms of the diffusion approximation ( * l occurs larger than 5 6 L L  ). Therefore, the spectral dependence   * l  was recovered using the inverse Monte Carlo (MC) modeling with the core MC algorithm repeatedly described in [33]. Figure 4 displays the recovered spectral dependencies of the transport mean free path for the examined water-impregnated matrix media in the spectral range from 500 nm to 900 nm.…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%
“…On the contrary, following from the data presented in Figure 3 for the SiO2-based system, it can be concluded that its diffuse transmittance cannot be adequately described in terms of the diffusion approximation ( * l occurs larger than 5 6 L L  ). Therefore, the spectral dependence   * l  was recovered using the inverse Monte Carlo (MC) modeling with the core MC algorithm repeatedly described in [33]. Figure 4 displays the recovered spectral dependencies of the transport mean free path for the examined water-impregnated matrix media in the spectral range from 500 nm to 900 nm.…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%